MANAJEMEN INVESTASI DI BANK SYARI'AH - Wasilul Chair (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
All business activities are always faced with two possibilities, namely the gain or loss so also in the investment world. Shari’ah  banks as intermediary institutions that one of its functions is financing  namely distribute financing to customers that is one of forms is fund investments with skim mudharabah the finance portfolio to the customer in one of its forms is a capital investment with skim mudaraba or Musharaka. Shari’ah banks in channeling funds  face the greater risk because of dealing directly with the customer characteristics. Thus, Shari’ah Banks taking the precautionary principle (prudential banking) in distributing funds are  the screening pattern on a prospective customer to avoid asymmetric information that can lead to moral hazard and adverse selection. The screening criteria using patterns 6A and 6C to minimize risk